Advocacy for Responsible Antibiotic Production and Use - Véronique Mondain; Nicolas Retur; Benjamin Bertrand; Florence Lieutier-Colas; Philippe Carenco; Sylvain Diamantis (MDPI AG, 2022)
Antibiotic-resistant bacteria have become one of humankind's major challenges, as testified by the UN's Call to Action on Antimicrobial Resistance in 2021. Our knowledge of the underlying processes of antibiotic resistance is steadily improving. Beyond the inappropriate use of antimicrobials in human medicine, other causes have been identified, raising ethical issues and requiring an approach to the problem from a "One Health" perspective. Indeed, it is now clear that the two main issues regarding the subject of antibiotics are their misuse in the global food industry and their method of production, both leading to the emergence and spread of bacterial resistance.